Pengaruh Mengonsumsi Garam Berlebihan Dengan Hipertensi Dan Proteinuria Di Puskesmas Jaten II Karanganyar - Liss Dyah Dewi Arini; Indra Agung Yudhistira; Etik Yuniarsih (Jurnal Kesehatan Komunitas, 2020)
Salt consumption is very necessary for humans to survive because the human body relies on sodium for muscle contraction, nerve transmission, and control systems to balance body fluids, along with other electrolytes such as potassium. Eating too much salt can be bad for health such as hypertension and proteinuria. Hypertension is a disorder of the circulatorysystem, which prey much disturbs public health. One of the complications of hypertension is kidney failure, proteinuriais one of its clinical manifestations. The general objective of this study is to determine the relationship of excessive salt consumption associated with the incidence of hypertension that connues to proteinuria in the Karanganyar Jaten II Health Center, while the specific objective is to find out the general description of the respondent's characteriscs and to find out the specific data of the respondent's characteriscs. This was a quantative observational study with a descriptive research design. The population in this study were all hypertensive patients in the Karanganyar Jaten II Health Center, amounting to 34 people. The sample in this study were all members of the populaon. The sampling technique used in this study was purposive sampling. This study concludes that consuming salt will result in an imbalanced balance of sodium and potassium, making it difficultfor the kidneys to work well with the appearance of proteinuria. Then, occurs the fluid retenon that followed by blood pressure increased. Keywords : Salt, proteinuria, hypertension, puskesmas.